Mycobacterium avium Subsp. avium Infection in Four Veal Calves: Differentiation from Intestinal Tuberculosis. (13th February 2014) - Goepfert, Christine; Regenscheit, Nadine; Schumacher, Vanessa; Roos, Simone; Rossier, Christophe; Baehler, Corinne; Schmitt, Sarah; Posthaus, Horst
Abstract : Mycobacterium avium subsp. avium (Maa) is an intracellular pathogen belonging to the Mycobacterium avium-intracellulare complex (MAC). Reservoirs of MAC are the natural environment, wildlife and domestic animals. In adult bovine, MAC infections are typically caused by Mycobacterium avium subsp. paratuberculosis (Map). Maa infections in bovine are rarely reported but may cause clinical disease and pathological lesions similar to those observed in paratuberculosis or those induced by members of the Mycobacterium tuberculosis complex (MTBC). Therefore, differentiation of MAC from MTBC infection should be attempted, especially if unusual mycobacterial lesions are encountered. Four veal calves from a fattening farm dying with clinical signs of otitis media, fever, and weight loss were submitted for necropsy. Samples from affected organs were taken for histologic investigation, bacteriologic culture, and bacterial specification using PCR. Macroscopic thickening of the intestinal mucosa was induced by granulomatous enteritis and colitis. Intracytoplasmic acid-fast bacteria were detected by Ziehl-Neelsen stains and PCR revealed positive results for Mycobacterium avium subsp. avium . Clinical and pathological changes of Maa infection in veal calves had features of Mycobacterium avium subsp. paratuberculosis and the MTBC. Therefore, Mycobacterium tuberculosis complex infection should be considered in cases of granulomatous enteritis in calves.